Cursos de música popular em universidades públicas brasileiras: realidades, perspectivas e diretrízes - Dantas, Leonardo Meira (2024)
This thesis aims to understand the structures and the main theoretical and methodological bases that have underpinned the pedagogical proposals and educational praxis of undergraduate courses in popular music at public universities in Brazil. The research was qualitative in nature and used bibliographical research and documentary research as data collection tools. The study universe is made up of popular music courses (Bachelor and License Degrees) currently offered in Brazil at the following institutions: UNICAMP, UNIRIO, UNESPAR, UFPB, UFMG, UFRGS, UFPEL, UFRN, UFRB, UFG. It presents an understanding of the identity of higher education within the characteristics of university education, discussing the dilemmas that have affected and continue to affect this level of education over time, its trajectory in Brazil, the inclusion of music teaching in this sphere and the arrival of popular music as a more contemporary phenomenon. It also presents a view of the phenomenon of popular music from a broader perspective, different from the idea commonly conveyed that relates it to the process of phonographic production, where this becomes the characteristic most considered within the courses that deal with the higher education of popular music. The thesis also discusses the different models that are used in the various processes that characterize the training of musicians inside and outside the higher education environment. In this sense, it points to the trajectory and characteristics of the different spaces that, as socially recognized institutions, welcomed popular music before its inclusion in the higher music courses offered by legitimized institutions, culminating in the undergraduate courses offered by public universities. With regard to the institutions that deal with higher education in popular music, it first presents a general overview of the reality of the courses that currently exist and, secondly, deepens the debate based on the data provided by the ten public universities that make up the universe of studies in this thesis. Thus, after analyzing the data and discussing the various authors who form the basis of this thesis, at the end it presents guidelines with curricular and pedagogical proposals to be incorporated in order to strengthen the consolidation of popular Brazilian music in higher education in the country.